HUBUNGAN KESULITAN BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS VII SMP NEGERI 26 MALANG - Nugroho Aji Prasetiyo; Aminarni Anace Dede; Yuswa Istikomayanti (Universitas Tribhuwana Tunggadewi, 2022)
The purpose of this study was to ascertain the relationship between the science learning outcomes of Class VII students at SMP Negeri 26 Malang with learning difficulties Low motivation, passivity in class, and difficulties during the discussion process are symptoms of learning difficulties found in science learning at SMP Negeri 26 Malang. Various symptoms of learning difficulties affect student science learning outcomes. This study used a quantitative approach, specifically the type of causal research and questionnaire or data collection of sperm rank correlation questionnaire data from respondents. The results of the study of internal factors and external factors are in the weak category. While scientific difficulties are included in the weak category. The decision to accept H0 leads to the conclusion that the relationship between learning difficulties and science learning outcomes is an insignificant or insignificant relationship. The results of the study relationship between learning difficulties and learning outcomes in the low category, the relationship of scientific learning difficulties with learning outcomes are also in the low category. Based on the correlation, Spearman showed that the results of the relationship between learning difficulties and learning outcomes were insignificant.